KEPEMIMPINAN LOKAL ERA PILKADA LANGSUNG - Utomo, Susilo (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2009)
The main purpose of this research is to answer problem â€œfigures leadership of Govermentâ€. Like what in idealizing by society-elector Central Java in election of governor Central Java 2008 ago. By using method research of survey including 6 sub-province / town, 18 district, 54 countryside / sub-district and 2400 responder, which taking pursuant to multi stage random sampling. In fact elected of Bibit Waluyo â€“ Rustriningsih in election of governor in Central Java because the couple have ideal leadership marking as which desiring by society-elector of Central Java, that is value local leadership society of Central Java.